The analysis of road safety in Slovenia in 2018 (Journal of Universal Excellence, 2026)
Research Question (RQ): What was the road safety situation in Slovenia in 2018?Purpose: The consequences of road accidents are material damage, injuries and fatal injuries. The aim of the research is to determine the threats of individual types of road users and their role in road accidents.Method: Secondary road traffic safety data of the Ministry of Interior for 2018 are used. The quantitative data are analysed with frequency statistics.Results: Pedestrians and motorcyclists are most at risk in road traffic.Organization: The results will help the Ministry of the Interior to act.Society: Increasing traffic safety means lower social costs due to road accidents.Originality: The survey is important for increasing road safety.Limitations/further research: Only data for 2018 are used.
Keywords: traffic; traffic safety; accident; bodily injuries; fatal injuries